Bonding interactions in congested molecules : a study of the interatomic forces and the molecular electrostatic potential - Von Berg, Stuart Raymond Colenzo (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD) -- Stellenbosch University, 2022.